Osteoblastic flare in a patient with advanced gastric cancer after treatment with pemetrexed and oxaliplatin: implications for response assessment with RECIST criteria - Simoncini Edda (BMC Cancer, 2007)
Abstract Background The RECIST guidelines are commonly used in phase II and III clinical trials. The correct definition of response can be controversial in some situations, as in the case we describe. Case presentation A 43 year-old man with advanced gastric cancer was enrolled in a phase II trial where he was treated with pemetrexed 500 mg/m2 plus oxaliplatin 120 mg/m2 every 3 weeks. At baseline, the target lesions were lymph-nodes, and the non-target lesions were small pulmonary nodules. At first re-evaluation, the target lesions showed partial response and the non-target lesions showed complete response, but new diffuse osteoblastic lesions appeared. The investigator decided to continue treatment until the second re-evaluation. CT scan confirmed the response of the target and non-target lesions, while the osteoblastic lesions did not change. Conclusion The appearance of osteoblastic lesions after an active antitumor treatment, a phenomenon known as flare, can complicate the definition of the best overall response using RECIST criteria. This possibility should be considered by oncologists involved in clinical trials.